The economy of Ethiopia : volume I and volume II - International Bank for Reconstruction and Development; International Development Association (Washington, D.C. : International Bank for Reconstruction and Development, 1963)
The book discusses the economy of Ethiopia
Volume II contains Appendices.
aia 10/04/2017
Loans
Keywords: Economy; Ethiopia